Determinants of dividend payout ratio by consumer sector in Malaysia / Najihah Ghazali@ A. Shukor - Ghazali@ A. Shukor, Najihah (2018)
Tax evasion defined as an illegal underpayment of taxes by individuals, corporations, as well as SMEs in Malaysia that intentionally avoids paying a true tax liability by misrepresenting the true state of their affairs to the tax authorities and includes dishonest tax reporting that specifically occur in the informal economy due to their characteristics and the nature of their business. Therefore, those who taught evading taxes are generally subject to criminal charges and substantial penalties. Compliance with tax laws must be strictly enforced and tax offences such as non-compliance and tax evasion should be penalized in accordance with the provisions of the Income Tax Act 1967 (ITA). Under the Self-Assessment System, tax audit is primary activities of the Inland Revenue Board of Malaysia (IRBM). This study investigate the factors that cause tax evasion among SMEs in Malaysia. According to Census report on SMEs 201 1, there was a total of 645, 136 SMEs operating their businesses in Malaysia. It is representing 97.3% of total business establishments. Wayne Lim is a Group CEO of Malaysia SME stated that "SME business from a very large part in Malaysia's economy, but their contribution to be a responsible tax payments group is still lacking compared to their counterparts in developed countries." Data were retrieving from IRBM's proprietary tax data for 30 years which is from 1987-2017 in order to identify either the contribution either it still lacking or vice versa from SMEs in Malaysia. We examine the relationship between SME's tax evasion by using ordinary least square regression. The variables under this study are type of industry and the use of tax agent, and the dependent is tax evasion. The methodology applied in this research is multiple regression analysis to examine the impact of the data.